Genotipos de resistencia antimicrobiana y su expresión fenotípica en cepas de Staphylococcus aureus - Castellano-González Maribel; Perozo-Mena Armindo; Parra Ana María; Ginestre-Pérez Messaria; Rincón-Villalobos Gresleida (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Abstract: Antimicrobial resistance was determined for 106 S. aureus strain isolates from patients treated in the Bacteriological Reference Center at the University Hospital Autonomous Service, Maracaibo, during the first trimester of 2009, using phenotypic and genotypic methods. Culture, isolation and identification were performed following conventional methodology. Phenotypically, 103 strains (97.17%) were resistant to penicillin G; 54 (50.94%) to methicillin; 43.39% to erythromycin (46) and 34.91% (37) to gentamicin. In addition, 13 (12.26%) were intermediate to erythromycin. Genotypically, 90 strains (84.91%) carried the blaZ gene through the polymerase chain reaction (PCR); 53 (50%) carried the mecA gene; only 10 (9.43%) harbored the gene aac(6')/aph(2''); the gene ermA was detected in 41 isolates (38.68%) and msrA in 17 (16.04%). The discordant results were: (1) A mecA-negative, but methicillin-resistant strain, which proved blaZ-positive and hyper-productive of B-lactamases; (2) An erythromycin-resistant strain, negative for ermA, B, C and msrA genes, and; (3) Twenty-six gentamicin-resistant strains, negative for aac(6')/aph(2''). The phenotypes and genotypes of antimicrobial resistance are related; however, there is a marked variability in the genetic determinants for resistance, which undoubtedly affects phenotypic ex- pression. For oxacillin and, to a lesser degree erythromycin, there is a good match between the resistance phenotypes and genotypes found, noting the greatest discrepancy in the aminoglycosides and penicillin G. Resumen: Se determinó la resistencia antimicrobiana mediante métodos fenotípicos y genotípicos a 106 cepas de S. aureus aisladas de pacientes atendidos en el Centro de Referencia Bacteriológica del Servicio Autónomo Hospital Universitario de Maracaibo durante el primer trimestre del 2009. El cultivo, aislamiento e identificación se realizó siguiendo la metodología convencional. Fenotípicamente, 103 cepas (97,17%) resultaron resistentes a penicilina G; 54 (50,94%) a meticilina; 43,39% a eritromicina (46) y 34,91% (37) a gentamicina. Además, 13 (12,26%) se mostraron intermedias a eritromicina. Genotípicamente, 90 cepas (84,91%) portaban el gen blaZ mediante la reacción en cadena de la polimerasa (PCR); 53 (50%) acarreaban el gen mecA; sólo 10 (9,43%) albergaban el gen aac(6')/aph(2''); el gen ermA se detectó en 41 aislados (38,68%) y msrA en 17 (16,04%). Los resultados discordantes fueron: (1) Una cepa mecA-negativa; pero resistente a meticilina, la cual resultó blaZ-positiva e hiperproductora de B-lactamasas; (2) Una cepa resistente a eritromicina y negativa para los genes ermA, B, C y msr y; (3) veintiséis cepas gentamicina-resistentes; pero negativas para aac(6')/aph(2''). Los fenotipos y genotipos de resistencia antimicrobiana están relacionados; sin embargo, existe una marcada variabilidad en los determinantes genéticos de la resistencia lo que repercute, indudablemente en su expresión fenotípica. Para oxacilina y en menor proporción para eritromicina, existe una buena concordancia entre los fenotipos y genotipos de resistencia encontrados; observándose la mayor discrepancia en los aminoglicósidos, y penicilina G.